Aristotle's theory of predication - Bäck, Allan. (Philosophia Antiqua, 2000)
This book claims that Aristotle followed an aspect theory of predication. On it statements make a basic assertion of existence that can be more or less qualified. It is claimed that the aspect theory solves many puzzles about Aristotle's philosophy and gives a new unity to his logic and metaphysics. The book considers Aristotle's views on predication relative to Greek philology, Aristotle's philosophical milieu, and the history and philosophy of predication theory. It offers new perspectives on such issues as existential import; the relation of Categories 2 andamp; 4; the place of differentiae and propria ; the predication of matter; unnatural predication; and the square of opposition. It ends by comparing Aristotle's theory with current ones.